2014
DOI: 10.1007/s13369-014-1504-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Acid–Rock Reaction Kinetics Under High Temperature and Pressure Conditions Based on the Rotating Disk Instrument

Abstract: In this paper, a rotating disk instrument was used to simulate the acid-rock reaction under high temperature and pressure reservoir conditions. By changing the reaction temperature, pressure, rotational speed and acid concentration, the reaction rate was measured first, and then the reaction parameters such as reaction rate constant, reaction order and effective mass transfer coefficient of H + were analyzed through data processing and regression analysis; reaction kinetics equation was therefore obtained, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…The mass loss percent ( R c ) decreased with the decrease in the acid concentration . As shown in Figures b and b, the mass loss percent and Ca dissolution of a part of the sample in the pH 2 solution were not increased with the increase in the disk speed.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The mass loss percent ( R c ) decreased with the decrease in the acid concentration . As shown in Figures b and b, the mass loss percent and Ca dissolution of a part of the sample in the pH 2 solution were not increased with the increase in the disk speed.…”
Section: Discussionmentioning
confidence: 84%
“…To analyze the influence of hydrodynamic conditions on the acid erosion of carbonate rocks, a self-made rotating rock plate reactor was used to carry out dynamic dissolution simulation experiments at room temperature and pressure conditions (Figure ). , The hydrochloric acid solution with a concentration of 67% was diluted with deionized water, and the acid solution with two concentrations of pH 1 and 2 was configured. The capacity of each group of the acid solution was 3500 mL.…”
Section: Methodsmentioning
confidence: 99%
“…The rotating disk instrument is widely used for gaining acid rock reaction kinetic parameters, such as acid consumption rate, reaction rate constants, reaction order, and activation energy (Anderson 1991;Fredd, 1998a;Alkattan et al, 1998;Fredd and Fogler, 1998b;Gdanski and Van Domelen, 1999;Frenier and Hill, 2002;Li et al, 2015). Downhole cores were cut into disks, and the acid solutions of 10wt% and 15wt% were allocated by 20 wt% fresh acid and CaMg(CO 3 ) 2 powder to consider the effect of Ca 2+ and Mg 2+ , for acid rock reaction kinetics experiments.…”
Section: Acid Rock Reaction Experimentsmentioning
confidence: 99%
“…Karst has received more and more attention from international scholars, and s research results have been achieved on carbonate rock dissolution experiments, which mainly focused on indoor simulation experiments. For example, Li, N.Y. et al [13], L et al [14], and Hyunsang et al [15] simulated the dissolution reaction indoors by usi rock disk rotating and moving relative to the solution; Erik B. Larson et al [16], in indoor study of carbonate dissolution rates, found that the petrography and minera of carbonate rocks affect their dissolution rates in a laboratory setting; Plummer et al found large differences in calcite dissolution rates and their mechanisms of change un different pCO2 conditions by studying the kinetic mechanisms of calcite dissolution doors; Yu, S. et al [18] showed that the dissolution rate of carbonate rocks was affecte rainwater acidity and rainfall via an experimental indoor dissolution study of carbo Karst has received more and more attention from international scholars, and some research results have been achieved on carbonate rock dissolution experiments, which are mainly focused on indoor simulation experiments. For example, Li, N.Y. et al [13], Li, Q. et al [14], and Hyunsang et al [15] simulated the dissolution reaction indoors by using a rock disk rotating and moving relative to the solution; Erik B. Larson et al [16], in an indoor study of carbonate dissolution rates, found that the petrography and mineralogy of carbonate rocks affect their dissolution rates in a laboratory setting; Plummer et al [17] found large differences in calcite dissolution rates and their mechanisms of change under different pCO 2 conditions by studying the kinetic mechanisms of calcite dissolution indoors; Yu, S. et al [18] showed that the dissolution rate of carbonate rocks was affected by rainwater acidity and rainfall via an experimental indoor dissolution study of carbonate rocks by acid rain in Guilin, China.…”
Section: Introductionmentioning
confidence: 99%